Tackling misperceptions about immigrants with fact-checking interventions: A randomized survey experiment - CHOI, Syngjoo (Institutional Knowledge at Singapore Management University, 2023)
We conduct a randomized online survey experiment to study the impact of fact-checking offers and financial incentives on misperceptions about immigrants. We find that natives overestimate the number of immigrants and the social and economic costs of immigration. Offering a free check of the factual information about immigrants reduces these misperceptions; it becomes more effective when combined with financial incentives. However, more than half of the participants never took up offers to check factual information. Using a model of information search with limited attention, we identify the presence of non-negligible costs of information search and processing, which limits the effectiveness of the fact-checking interventions. Finally, we find that the fact-checking interventions moderately improve natives' attitudes toward immigrants but affect neither their policy preferences nor giving behavior toward immigrants.